Analisis Kebijakan Dan Tata Kelola Desa Wisata Di Kabupaten Sinjai - Atifah Hikmawati; Umar Congge; Fitrawati AB (Universitas Mbojo Bima, 2026)
This study aims to analyze the policies and governance of tourism villages in Sinjai Regency. The method used is a qualitative approach through in-depth interviews and direct observation of local governments, village governments, tourism village managers, and the community. The results of the study indicate that the direction of tourism village development policies in Sinjai Regency has had local potential-based planning through official regulatory basis, namely Regent's Decree Number 156 of 2020. Area arrangement is carried out through potential identification and administrative selection. Management is facilitated through training and mentoring programs from the Tourism Office. Supervision is carried out in a participatory manner through field visits and reporting, but the supervision aspect has not been supported by a sustainable monitoring system. Tourism village governance shows dynamics between villages in institutional capacity, potential attractions, availability of amenities, quality of human resources, partnerships, and promotional strategies. Panaikang Village shows institutional functioning, attraction management, and partnerships. Barania Village shows human resource strengthening and active promotion, while Tompobulu Village faces challenges in institutions and infrastructure. Synergy between the Regional Government and Village Governments has been established, but remains limited by budget constraints, capacity constraints, and suboptimal promotion. The conclusion of this study confirms that although tourism villages in Sinjai Regency have a policy and institutional framework that supports the development of sustainable destinations based on local potential, increased inter-institutional synergy, innovation in promotion, and strengthening of infrastructure and oversight are needed to ensure sustainable development, regional competitiveness, and optimal economic and social benefits for village communities.